Political Culture and Voting Behavior in New Delhi: A Case Study of Aam Admi Party (2013–2020) - Shabbir, Asma; Nawaz, Muhammad Waqas (Journal of Development and Social Sciences, 2025)
The study analyses the transformation of political culture and voting behavior in New Delhi between 2013 and 2020 focusing on the emergence and rise of the Aam Aadmi Party. The aim of the research is to examine how voter preferences shifted in New Delhi politics and what factors contributed to the rise of Aam Aadmi Party. This is primarily qualitative, analytical and comparative study. It employs comparative case study method to examine the Delhi Legislative Assembly elections of 2013, 2015, and 2020. The analysis is based on Almond and Verba’s theoretical model of Civic Culture. The study finds that New Delhi’s political culture has change from traditional to issue oriented and identity-based politics. The study concludes that the political culture of New Delhi has evolved toward a more performance and issue focused model which challenged traditional identity politics. Aam Aadmi Party success illustrates a broader trend of urban democratic realignment, where governance outcomes and transparency have become key determinants of voter behavior.